ANALYSIS OF THE TECHNOLOGICAL EFFORT OF CONNECTING BRIDGE DESTRUCTION DURING PACKAGING MANUFACTURING WITH FLAT DIE-CUTTING PRESSES - Лойзик, Владислав; Бриндас, Андрій; Терницький, Сергій (SWorldJournal, 2025)
The article considers a pressing problem in the packaging industry related to optimising post-press processing of paperboard blanks, particularly waste removal and cut-outs separation. An analysis of scientific and technical literature was conducted, whic